НИКОҲДАН ТАШҚАРИ МУНОСАБАТЛАРНИНГ ОИЛА МУСТАҲКАМЛИГИГА ТАЪСИРИ - Абдусаматов, Х.У. (FAN va JAMIYAT, 2018)
The article is devoted to the description of social-psychological peculiarities of extramarital relationships that lead to divorces in families. The author of the article also studied the reasons of extramarital relationships and shows at what level this problem has been studied in the works of foreign scientists.